Experimental models to unravel the molecular pathogenesis, cell of origin and stem cell properties of cholangiocarcinoma. (20th May 2019) - Vicent, Silvestre; Lieshout, Ruby; Saborowski, Anna; Verstegen, Monique M. A.; Raggi, Chiara; Recalcati, Stefania; Invernizzi, Pietro; van der Laan, Luc J. W.; Alvaro, Domenico; Calvisi, Diego F.; Cardinale, Vincenzo
Abstract: Human cholangiocarcinoma (CCA) is an aggressive tumour entity arising from the biliary tree, whose molecular pathogenesis remains largely undeciphered. Over the last decade, the advent of high‐throughput and cell‐based techniques has significantly increased our knowledge on the molecular mechanisms underlying this disease while, at the same time, unravelling CCA complexity. In particular, it becomes clear that CCA displays pronounced inter‐ and intratumoural heterogeneity, which is presumably the consequence of the interplay between distinct tissues and cells of origin, the underlying diseases, and the associated molecular alterations. To better characterize these events and to design novel and more effective therapeutic strategies, a number of CCA experimental and preclinical models have been developed and are currently generated. This review summarizes the current knowledge and understanding of these models, critically underlining their translational usefulness and limitations. Furthermore, this review aims to provide a comprehensive overview on cells of origin, cancers stem cells and their dynamic interplay within CCA tissue.